Magnetic characteristics of Chinese archaeological bricks and their implications for archaeomagnetism - Chen, Qiong; Sun, Qirui; Liao, Lishan; Wang, Wei; Yang, Xiaoqiang (Frontiers in Earth Science, 2023)
Fired archaeological objects have been widely studied in palaeomagnetic research. However, the uneven heating during the firing process can affected the type, grain size and magnetic domain characteristics of the magnetic carrier, which in turn can led to notable discrepancies in the paleomagnetic information that they captured. In this study, we conducted a detailed rock magnetic study on two Chinese archaeological (one grey and one red) to reveal the properties of magnetic minerals subjected to different firing temperatures. Our results show that single domain (SD) magnetite with strong magnetostatic interactions is the dominant magnetic carrier in grey bricks, while SD magnetite with weak magnetostatic interactions is the dominant magnetic carrier in the red bricks. And stepwise heating results show that the firing temperature of the grey brick and the outer layers of red brick (R-1, R-3) is above 700°C, while the inner layer (R-2) of red brick shows a thermal transformation process at ∼ 350°C. This uneven heating may cause the spatial discrepancies in magnetic parameters such as the mass-normalized magnetic susceptibility (χ) and natural remanent magnetization (NRM) in red brick. Nevertheless, the direction of the geomagnetic field can be accurately obtained even if the brick is not heated evenly. However, more work is needed to explore the paleointensity behavior at different firing temperatures.